Increasing the oxidative stability of linseed oil - Sytnik, Natalia; Korchak, Mykola; Nekrasov, Serhii; Herasymenko, Vitalii; Mylostyvyi, Roman; Ovsiannikova, Tetiana; Shamota, Tetiana; Mohutova, Valentyna; Ofilenko, Nataliia; Choni, Inna (Technology center PC, 2023)
The object of the research is the process of oxidation of linseed oil at elevated temperature. Linseed oil is a valuable raw material for the chemical, food, cosmetic and other industries. The use of linseed oil is complicated by intensive oxidation processes associated with a high content of unsaturated fatty acids. Therefore, an important task is to develop and improve methods of oxidative stabilization of linseed oil. The oxidation process of unrefined linseed oil (CAS Number 8001-26-1) at a temperature of 110 °C in its original form and with the addition of antioxidants was studied. The effect of antioxidant concentrations (tocopherol, butylhydroxyanisole and butylhydroxytoluene) in the mixture on the induction period of linseed oil was found. The induction period was determined by differential scanning calorimetry. The total concentration of the mixture of antioxidants in each experiment was 0.02 %. The induction period of the initial oil was 155.31 min. Rational ratios of antioxidants in the mixture were found: tocopherol: butylhydroxyanisole (50:50) %; tocopherol: butylhydroxytoluene (50:50) %; tocopherol: butylhydroxyanisole: butylhydroxytoluene (33.33:33.33:33.33) %. At the same time, the oil induction periods are 295.7 min., 290.1 min. and 290.2 min., respectively. The quality indicators of the initial linseed oil and with the addition of the determined rational ratios of antioxidants after 2 hours of aging at a temperature of 110 °C were determined. The peroxide values of the samples were 8.5, 3.2, 3.6, 3.7 ½ O mmol/kg, respectively. The research results make it possible to introduce antioxidants in the production of linseed oil in rational concentrations. This will help increase the production of linseed oil resistant to oxidation at elevated temperatures, which will provide various industries with high-quality raw materials.
Keywords: linseed oil; free-radical process; oxidative stability; induction period; oxidation inhibitor